The Importance of a Rhetorical Approach for the Historically Informed Performance of Music: 1740–1830 - Muskens, Anders (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2023)
During the period 1740–1830, the classical art of rhetoric was still largely connected to music. Eighteenth-century theorists emphasized crucial links between rhetoric and the musical arts. Each mode of expression informed the other, with common goals of expressing, communicating, and persuading. Rhetoric guided musical composers and performers alike, who sought to capture the hearts and minds of listeners through artistic expression. However, such principles arguably deserve more attention in modern musical education and performances of this repertory. This essay outlines some basic principles behind a rhetorical approach to eighteenth-century music for modern musical performers in the historically informed performance field.